Effect of capillary adhesion on fracture of photovoltaic silicon wafers during diamond wire slicing. (15th May 2022) - Zheng, Jintao; Ge, Peiqi; Bi, Wenbo; Zhao, Yukang; Wang, Chao
Graphical abstract: Highlights: A hierarchical capillary adhesion model of wafers during diamond wire slicing is presented. Capillary adhesion has a greater effect on the large and thin wafers slicing with a fine wire. Capillary adhesion significantly increases the risk of wafer fracture for thickness below 100 μm. As wafer thickness decreases to 50 μm, the 210 × 210 mm 2 mono-Si wafer fracture probability caused by capillary adhesion increases to more than 6%. Abstract: As the photovoltaic industry needs to reduce manufacturing costs, the kerf loss and the wafer thickness of diamond wire slicing will be further reduced in the future, which will make the spacing and bending rigidity of the wafers decrease to the extent that the effect of capillary adhesion of wafers is more significant during slicing, thus increasing the risk of silicon wafer fracture. Therefore, a hierarchical capillary adhesion model of wafers during the diamond wire slicing based on the principle of minimum potential energy is established in this paper. The variation of the maximum bending stress and the number of adhered wafers with sawing depth, kerf width, and wafer thickness and the effect of capillary adhesion on the silicon wafer fracture are studied. The results show that the maximum bending stress and the number of adhered wafers increased with the increase of the sawing depth, which meant that the risk of wafer fracture was greater for sawing large-sized wafers. And they also tended to increase as the kerf width and the wafer thickness decreased, that was, the effect of capillary adhesion on the thin wafer sawn with a fine diamond wire was more significant. In addition, the probability of the mono-Si wafers fracture caused by capillary adhesion increased significantly when the wafer thickness was less than 100 μm. The research work is of great significance for further research on the thin wafers slicing technology with the fine diamond wire to reduce the manufacturing costs of silicon wafers in the photovoltaic industry.